Diseño de un sistema de supervisión y automatización para la subestación "Los Pinos" de la ciudad de Machala. - Bustamante Duque, Carlos Fernando (2008)
The present research project was carried out thanks to the collaboration of the Electric Company EMELORO of the Machala city specifically for the Substation “Los Pinos” of 69/13.8 kV, in which different alternatives are captured for improvement of the electric power service, by means of the employment of a supervision and automation system. The work is based firstly, in the implementation of digital relays for protection and acquisition both of the transformer of 16/20 MVA and of each one of the feeders located in the side of low voltage; it also intends to use a PLC to acquire the opening and closing signs of the motorized disconnecting switchs that are located in the place of 69 kV. All these signs will be taken to a Software SCADA, which will take charge of supervising in real time the operating statement of the Substation, allowing this way the taking of decisions in the moment that some anomaly is raised inside the system.